DREF plays multiple roles during Drosophila development. - Tue, N.T.; Yoshioka, Y.; Mizoguchi, M.; Yoshida, H.; Zurita, M.; Yamaguchi, M. (Biochimica et Biophysica Acta, 2017)
DREF was originally identified as a transcription factor that coordinately regulates the expression of DNA replication- and proliferation-related genes in Drosophila. Subsequent studies demonstrated that DREF is involved in tumor suppressor pathways including p53 and Hippo signaling. DREF also regulates the expression of genes encoding components of the JNK and EGFR pathways during Drosophila development. DREF itself is under the control of the TOR pathway during cell and tissue growth responding to nutrition. Recent studies revealed that DREF plays a role in chromatin organization including insulator function, chromatin remodeling, and telomere maintenance. DREF is also involved in the regulation of genes related to mitochondrial biogenesis, linking it to cellular proliferation. Thus, DREF is now emerging as not only a transcription factor, but also a multi-functional protein. In this review, we summarize current advances in studies on the novel functions of Drosophila DREF.